Factors Influencing the Decision to Buy Houses in Tangerang City, Indonesia: An Examination of Property Features, Superior Service, and Buying Intentions - Johan Budiman,; Juhary Ali,; Hindardjo, Anton (Technium Social Sciences Journal, 2024)
This study delves into the complex factors influencing house-buying decisions in Tangerang City, Banten, Indonesia, mainly focusing on the unique challenges brought about by the COVID-19 pandemic. Employing R-Square (R2) and predictive relevance (Q2) analyses, the research seeks to thoroughly evaluate the impact of independent variables on dependent variables, illuminating the factors and consequences of buying decisions in these unprecedented times. The R-Square analysis, conducted using SmartPLS, reveals that ownership determinants (X1) and service excellence (X2) are together. This study enhances our knowledge of real estate market trends under the difficult circumstances of the COVID-19 pandemic. The practical findings offer valuable insights for improving marketing approaches, enhancing customer interactions, and adjusting to changing external conditions, thus aiding in developing more effective policy assistance